Identifying dimensions of fatigue in haemodialysis important to patients, caregivers and health professionals: An international survey. Issue 3 (16th August 2019) - Ju, Angela; Unruh, Mark; Davison, Sara N; Dapueto, Juan; Dew, Mary A; Fluck, Richard; Germain, Michael; Jassal, Sarbjit V; Obrador, Gregorio; O'Donoghue, Donal; Howell, Martin; O'Lone, Emma; et al.
ABSTRACT: Background: Patient‐reported outcome measures of fatigue used in research in haemodialysis vary widely in the dimensions assessed; and the importance of these dimensions to patients and health professionals is unknown. This study aimed to identify the most important dimensions of fatigue to assess in patients on haemodialysis participating in trials. Methods: In an international survey, patients/caregivers and health professionals rated the absolute and relative importance of content and measurement dimensions to include in a core outcome measure of fatigue. A 9‐point Likert scale (7–9 indicating critical importance) was used to assess absolute importance and best‐worst scale was used to assess importance of each dimension compared to others. Results: In total, 169 patients/caregivers and 336 health professionals from 60 countries completed the survey. Both groups (patients/caregivers and health professionals) rated life participation (7.55), tiredness (7.40), level of energy (7.37), ability to think clearly (7.15), post‐dialysis fatigue (7.13), motivation (7.03) and ability to concentrate (7.03) as critically important (mean Likert score greater than 7) content dimensions to include in a core outcome measure. Compared to patients and caregivers, health professionals rated post‐dialysis fatigue, memory and verbal abilities more highly. Based on the relative importance scores, life participation was ranked most highly above all content dimensions. Severity was rated and ranked the most important measurement dimension by all stakeholders. Conclusion: A core outcome measure of fatigue should assess impact of fatigue on life participation, tiredness and level of energy, using a severity scale. A consistent and valid measurement of fatigue will improve the value of trials in supporting decision‐making based on this important outcome. SUMMARY AT A GLANCE: Fatigue is a prevalent symptom in uraemic patients on haemodialysis and has multiple aetiologies. The authors derived a consensus of fatigue dimensions that could improve subsequent research aimed at addressing the issue of fatigue in this cohort of patients.